BOOTSTRAPPING SINTAKSIS PADA PERKEMBANGAN BAHASA ANAK USIA DINI - Nur Lailiyah; Yolanda Rensia Gigik (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2024)
This present study examines the process of syntactic bootstrapping in toddlers, focusing on how children utilize sentence structure to understand the meaning of new words. Syntactic bootstrapping is considered an important mechanism in language acquisition, where children use their developing syntactic knowledge to infer the meaning of unfamiliar words. This longitudinal study involved 15 toddlers aged 2-4 years, who were followed over a year. Through a series of experimental procedures, we tested the children`s ability to use syntactic information to interpret verbs. The results indicate that syntactic bootstrapping ability developed significantly over the study period. Children showed an increased ability to use argument structures to infer the meaning of verbs. Regression analysis revealed a positive correlation between syntactic bootstrapping ability and vocabulary size, suggesting a reciprocal relationship between syntactic and lexical development. Moreover, individual differences in syntactic bootstrapping ability were related to variations in the linguistics input children into the mechanism underlying early language acquisition and highlight the importance of syntactic bootstrapping in word learning. The implications of this study are relevant to theories of language development, early language intervention, and language teaching strategies. Theoretically, this current research can serve as a basis for educational interventions for children who show delays in language development.